Antibody blockade of IL‐17 family cytokines in immunity to acute murine oral mucosal candidiasis. Issue 6 (1st June 2016) - Whibley, Natasha; Tritto, Elaine; Traggiai, Elisabetta; Kolbinger, Frank; Moulin, Pierre; Brees, Dominique; Coleman, Bianca M.; Mamo, Anna J.; Garg, Abhishek V.; Jaycox, Jillian R.; Siebenlist, Ulrich; Kammüller, Michael; et al.
Abstract : OPC requires IL‐17R signaling in mice and humans; IL‐17A, but not IL‐17F blockade, predisposes to OPC, and functional redundancy among cytokines is evident. Abstract : Antibodies targeting IL‐17A or its receptor, IL‐17RA, are approved to treat psoriasis and are being evaluated for other autoimmune conditions. Conversely, IL‐17 signaling is critical for immunity to opportunistic mucosal infections caused by the commensal fungus Candida albicans, as mice and humans lacking the IL‐17R experience chronic mucosal candidiasis. IL‐17A, IL‐17F, and IL‐17AF bind the IL‐17RA‐IL‐17RC heterodimeric complex and deliver qualitatively similar signals through the adaptor Act1. Here, we used a mouse model of acute oropharyngeal candidiasis to assess the impact of blocking IL‐17 family cytokines compared with specific IL‐17 cytokine gene knockout mice. Anti‐IL‐17A antibodies, which neutralize IL‐17A and IL‐17AF, caused elevated oral fungal loads, whereas anti‐IL‐17AF and anti‐IL‐17F antibodies did not. Notably, there was a cooperative effect of blocking IL‐17A, IL‐17AF, and IL‐17F together. Termination of anti‐IL‐17A treatment was associated with rapid C. albicans clearance. IL‐17F‐deficient mice were fully resistant to oropharyngeal candidiasis, consistent with antibody blockade. However, IL‐17A‐deficient mice had lower fungal burdens than anti‐IL‐17A‐treated mice. Act1‐deficient mice were much more susceptible to oropharyngeal candidiasis than anti‐IL‐17A antibody‐treated mice, yet anti‐IL‐17A and anti‐IL‐17RA treatment caused equivalent susceptibilities. Based on microarray analyses of the oral mucosa during infection, only a limited number of genes were associated with oropharyngeal candidiasis susceptibility. In sum, we conclude that IL‐17A is the main cytokine mediator of immunity in murine oropharyngeal candidiasis, but a cooperative relationship among IL‐17A, IL‐17AF, and IL‐17F exists in vivo. Susceptibility displays the following hierarchy: IL‐17RA‐ or Act1‐deficiency > anti‐IL‐17A + anti‐IL‐17F antibodies > anti‐IL‐17A or anti‐IL‐17RA antibodies > IL‐17A deficiency.